The Effect Of Giving Honey on Hemoglobin Among School-Aged In Children In Carita Area, District Pandeglang, Banten - Putri Pertiwi, Lusiyana; Mutiariami Dahlan, Febry; Azzahroh, Putri (Rajaki of Tulip Medika Publisher, 2024)
Based on existing data in Indonesia it is 13.4% and in Banten it is 85.5%. The prevalence of anemia among children in Asia reached 58.4%, this figure is higher than the average in Banten (49.8%). If anemia is not treated properly, it makes it difficult for school-aged children to concentrate, besides that, school-aged children will look pale, often tired, weak, and their immune system will decrease. One way of fulfilling nutrition that can increase hemoglobin levels is by consuming honey, so it is important to improve the nutrition of school-aged children who experience anemia. This study aims to determine the effect of giving honey on hemoglobin among school-aged in children in Carita area, district Pandeglang, Banten in 2023. The research used a pre and post-test design with control group research design. The population in this study was 30 people. The sample used in this study was 30 school age children who were divided into two groups, namely 15 people as the intervention group and 15 people as the control group. The results of univariate analysis before and after being given honey averaged 9.90 mg/dl and after 12.50 mg/dl. In the control group before and after the average was 9.78 mg/dl and after 11.70 mg/dl. There is the effect of giving honey on hemoglobin among school-aged in children in Carita area, district Pandeglang, Banten in 2023 with a significance value of 0.000. There is an effect of giving honey on hemoglobin in school-aged in children. With this research, it is hoped that teachers in schools can provide information to their students so they can consume honey to increase hemoglobin levels in school-aged children. It is hoped that parents of school-age children will be able to provide honey for their children.